Assessment of Effectiveness of Science and Technology Projects: A Case Study of National Science and Technology Programme for Sustainable Development of North West Vietnam - Nhuan, Mai Trong; Cu, Truong Xuan; Ha, Nguyen Thi Hoang; Quy, Tran Dang; Linh, Pham Thuy; Tue, Nguyen Tai; Dung, Luu Viet (VNU Journal of Science: Earth and Environmental Sciences, 2020)
The present research was conducted to propose the index for assessing the effectiveness of science and technology projects in Vietnam. The effectiveness of projects was measured through 20 variables of 03 indicators: (1) The effectiveness of science and technology values including 12 variables; 2) The effectiveness of human resources including 04 variables; 3) and the effectiveness of education and training including 04 variables. These variables were evaluated by the 0-1 scale, with the zero-value indicated ineffectiveness of projects and vice versa. These variables were measured by the number of results, products from selected projects, and compared with the actual value in the project contract. Total 8 projects (including natural sciences, social sciences and technology projects) from National Science and Technology Program for Sustainable Development of North West Vietnam (NSTP-SDNW) were selected from 58 projects of NSTP-SDNW for testing the present index. Research results showed that the number of results and products of all projects have been met or exceeded requirements in project contracts. The assessment value of social projects (code 06X, 07X, 17X) ranged from 0.55 to 0.75, whereas the assessment value of natural sciences and technology projects ranged from 0.55 to 0.72. Research results showed that all selected projects are measured as high effective level, with the highest effectiveness was observed in No. 06X and No. 02C projects.